Scrutinizing Intrinsic Oxygen Reduction Reaction Activity of a Fe−N−C Catalyst via Scanning Electrochemical Cell Microscopy. Issue 6 (15th February 2023) - Limani, Ndrina; Batsa Tetteh, Emmanuel; Kim, Moonjoo; Quast, Thomas; Scorsone, Emmanuel; Jousselme, Bruno; Schuhmann, Wolfgang; Cornut, Renaud
Abstract: Carbon‐based nanomaterials are renowned for their exceptional properties, making them propitious candidates for oxygen reduction reaction (ORR) electrocatalysis. However, their intrinsic activity is often challenging to investigate unambiguously with conventional methodologies due to the inherent complexities of such systems and the material itself. Zooming into the material and gaining electrochemical information with high resolution is a way to get rid of many experimental factors that influence the catalytic activity in macro‐scale measurements. Herein, we employ nano‐scale scanning electrochemical cell microscopy (SECCM) to investigate individual catalyst agglomerates with and without Nafion content. The intrinsic ORR activity of the catalyst was unravelled by using a unique approach of normalizing the data of all measured points by their distinctive electrochemical surface area (ECSA). When coupling with scanning electron microscopy (SEM), the structure and morphology of the catalytically active agglomerates were visualized. Abstract : Unravel the intrinsic activity : Herein, we explicate the intrinsic oxygen reduction reaction activity of a Pt‐free catalyst via electrochemical surface area (ECSA) normalized data with scanning electrochemical cell microscopy (SECCM). A combination with scanning electron microscopy (SEM) performed on the same location enabled the structure visualization of the catalytically active agglomerates.